Da mente ao coração: as emoções na jornada de aquisição de serviços de comunicação empresarial no B2B - Silva, Ana Carolina David da (2022)
Emotions play a key role in determining business results in various sectors. Its function as cause, effect, mediation, and moderation of behavior has been a central element in marketing literature, especially in business-to-consumer (B2C) relations. However, in business-to-business (B2B) context, previously seen as rational, utilitarian, and functional, the systematic literature review indicated a recent paradigm shift in B2B by recognizing the influence of emotions on brand, sales-buyer dyad, purchase decision-making, relationships, and service experiences. This study sought to investigate the different emotions arising from B2B customer experience at each stage of the journey and specifically addressed the acquisition of business communication services. The phenomenological research was adopted through interviews with 7 marketing managers from companies across different sectors, deriving in 86 transcribed pages. The results allowed the development of a B2B customer journey map, which identifies processes, touchpoints, actors involved, expectations and emotions in the pre-purchase, purchase, and post-purchase stages. It also pointed out the presence of five emotions manifested in response to stimuli and situations experienced along the journey: fear, sadness, anger, joy, and surprise. This study innovates and contributes to the state of the art on organizational buying behavior as it approaches relational transactions from B2B customer journey’s perspective and focus on the emotions within it. By recognizing this latent aspect, managers can design marketing and relationship strategies that consider positive and negative emotional triggering events and, thus, adjust their offers to create value in B2B relations.